1999
DOI: 10.1007/s11746-999-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Deodorization of vegetable oils. Part I: Modelling the geometrical isomerization of polyunsaturated fatty acids

Abstract: Laboratory-scale treatments of canola oils similar to deodorization were carried out by applying the following conditions: reduced pressure with nitrogen or steam stripping at different temperatures ranging from 210 to 270°C for 2-65 h. The formation of the group of trans linolenic acid isomers follows a firstorder reaction and the kinetic constant varies according to the Arrhenius' law. Similar results were observed for the trans isomerization of linoleic acid. Based on these experiments, a mathematical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
2
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 8 publications
(16 reference statements)
3
63
2
2
Order By: Relevance
“…A deodorization temperature of 220-230 o C seems to be the critical point above which C18:3 acid isomerization substantially increases. The critical temperature is higher for C18:2 acid, over 240 o C (Henon et al, 1999). Kellens (1997) reported that chemical refining should be done at [230][231][232][233][234][235] o C and physical refining at 235-240 o C to obtain deodorized oils with low levels of trans FA (Ͻ 1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A deodorization temperature of 220-230 o C seems to be the critical point above which C18:3 acid isomerization substantially increases. The critical temperature is higher for C18:2 acid, over 240 o C (Henon et al, 1999). Kellens (1997) reported that chemical refining should be done at [230][231][232][233][234][235] o C and physical refining at 235-240 o C to obtain deodorized oils with low levels of trans FA (Ͻ 1%).…”
Section: Resultsmentioning
confidence: 99%
“…Refining has the purpose of not only eliminating impurities, but also minimizing trans FA formation (Kellens, 1997). Because the quality variables for refined vegetable oils include the lowest possible content in trans fatty acids, this is more and more important as a contemporary quality criterion (Leon-Camacho et al, 1999;Henon et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed composition of the diets is presented in Tables I and II. The diets were prepared from oil mixtures kindly provided by Lesieur (Coudekerque-Branche, France). Briefly, bleached canola oil was used after deodorization for 52.5 h at 205 • C under 3 mbar [28] to provide trans α-linolenic acid. Isomerized sunflower oil (270 • C, 18 h) was added in the mixtures in order to balance the trans linoleic acid (18:2 n-6) levels.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Each process is evaluated for its effectiveness at removing contaminants (pesticide residues, heavy metals) and unwanted compounds (prooxidative metals, degradation products) and the risk of formation unwanted compound (trans fatty acids dimer, trimer, polymer). (For more details of our results see [1][2][3][4]6]. )…”
Section: Best Available Techniquementioning
confidence: 99%